Analisis Perhitungan Overall Equipment Effectiveness pada Mesin Die Cut di PT. Empat Perdana Carton - Dhani Ilham Abdilah; Agustian Suseno (Jurnal Serambi Engineering, 2023)
AbstractCompanies must be able to compete with their rivals in the Industrial 4.0 age by boosting productivity. In manufacturing, machinery is typically only used for about 50% of its real capacity. One of the production equipment of PT. Empat Perdana Carton whose performance will be assessed is the die-cut machine. The Overall Equipment Effectiveness method is used to calculate the availability, performance, and quality values combined to generate the average value for measuring the performance of die-cut machines. According to the study's findings, the average availability ratio was 88.89%, the performance rate was 73.90%, the quality rate was 99.73%, and the OEE value was 65.63%. The lack of attention paid to repairs, the difficulty in locating machine parts, the lack of SOP application when using the machine, the unrealized work system, and the poor cleaning of scrap are the causes of the low OEE score.Keywords: overall equipment effectiveness, die cut machine, fishbone diagram, total productive maintenance